Periwayatan Hadis Bi Al-Lafzi dan Bi Al-Ma'na - Istianah, Istianah (RIWAYAH, 2015)
Abstract Often found in the books of hadith there are differences in the editorial of honor a tradition regarding the same issue. It due to the existence of hadith narration conducted its meaning, not based on the same wording as that related by the Prophet. Hadith narration done significantly is as the cause of the difference in the editorial of a tradition. In a hadith narration which allows for narrating pronunciation (riwayat bi al- lafz), just  traditions  in  the form of the word (AQWA l ar-Rasul). While the traditions that are not in the form of words, such as af’al (deeds) and taqri r (statutes) is only possible in the meaning narrated (history of bi al-ma’na). Traditions in the form AQWAl (word) was not entirely narrated by al-lafz bi} i. It is not possible due to the Prophet’s entire literally memorized by the companions and the tabi’in. It is because not all companions have the ability to memorize the same. This provides opportunities for editorial differences and variations in the understanding of the editorial hadith received from the Prophet. So it will take effect when they narrated to friends who had not heard directly from the Prophet.There  are various opinions of Hadith narration bi al-ma’na. some of them did not allow it absolutely. The layman is prohibited to convey tradition bi al-ma’na, in order to maintain the truth of tradition. As for the scholars of hadith were allowed to narrate bi al-ma’na, with certain conditions, so it will avoid mistakes. And not a word that is in the form of Jawarmi ‘al-Kalim. The existence of various provisions of the hadith indicates that transmission of hadith bi al-ma’na is allowed by some scholars, but in practice it is not “loose”. It means that they are not free to do a narration in meaning.